1983
DOI: 10.1159/000121488
|View full text |Cite
|
Sign up to set email alerts
|

Location of Motoneurons Innervating Soft Palate, Pharynx and Upper Esophagus. Anatomical Evidence for a Possible Swallowing Center in the Pontine Reticular Formation

Abstract: Retrograde HRP studies indicated that motoneurons innervating soft palate and pharynx are located in especially the dorsal group of the nucleus ambiguus, while motoneurons innervating upper esophagus and cricothyroid muscles are located in the retrofacial nucleus, the most rostral part of the nucleus ambiguus. Autoradiographic tracing techniques revealed that in the caudal pontine tegmentum an area is located just dorsal to the superior olivary complex, that projects contralaterally to the ventral part of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
42
0

Year Published

1990
1990
2014
2014

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 87 publications
(44 citation statements)
references
References 23 publications
2
42
0
Order By: Relevance
“…This "chewing pattern generator" projects to the motor trigeminal, mesencephalic trigeminal, and supratrigeminal nuclei (see Holstege et al, 1983;ter Horst et al, 1991;Li et al, 1993;Mogoseanu et al, 1993;Turman and Chandler, 1994;Chandler, 1999). Substantial BSTrh projections to more caudal regions of the parvicellular reticular nucleus may innervate central pattern generators for licking and swallowing (see Holstege et al, 1983;Travers and Norgren, 1983;Fay and Norgren, 1997a-c;Li et al, 1997;Travers et al, 1997;Cunningham and Sawchenko, 2000). In addition to direct inputs to orofaciopharyngeal pattern generator networks, the BSTrh may influence them less directly via massive inputs to the nucleus of the solitary tract and parabrachial nucleus, both of which project massively to the pattern generators (see Herbert et al, 1990;Whitehead, 1994;Karimnamazi and Travers, 1998).…”
Section: Functional Implications: Projection Targetsmentioning
confidence: 99%
“…This "chewing pattern generator" projects to the motor trigeminal, mesencephalic trigeminal, and supratrigeminal nuclei (see Holstege et al, 1983;ter Horst et al, 1991;Li et al, 1993;Mogoseanu et al, 1993;Turman and Chandler, 1994;Chandler, 1999). Substantial BSTrh projections to more caudal regions of the parvicellular reticular nucleus may innervate central pattern generators for licking and swallowing (see Holstege et al, 1983;Travers and Norgren, 1983;Fay and Norgren, 1997a-c;Li et al, 1997;Travers et al, 1997;Cunningham and Sawchenko, 2000). In addition to direct inputs to orofaciopharyngeal pattern generator networks, the BSTrh may influence them less directly via massive inputs to the nucleus of the solitary tract and parabrachial nucleus, both of which project massively to the pattern generators (see Herbert et al, 1990;Whitehead, 1994;Karimnamazi and Travers, 1998).…”
Section: Functional Implications: Projection Targetsmentioning
confidence: 99%
“…Cell bodies of these somatic nerves are situated in the brain stem, specifically in a region of the rostral nucleus ambiguus called the compact formation or the retrofacial nucleus [5][6][7][8][9]. Axons from these cell bodies pass uninterrupted as part of the vagus nerves to innervate the striated muscle of the esophagus.…”
Section: Striated Muscle Regionsmentioning
confidence: 99%
“…In fact, the corticoreticular projection from the ventral region of M1 and adjacent ventrolateral premotor cortex in the monkey has been shown to be quite extensive (Kuypers 1958a). Other related work has shown that premotor neurons in the pontine and medullary parvocellular reticular formation project directly to the hypoglossal nucleus (Holstege and Kuypers, 1977; Holstege et al, 1977, 1983). Specifically, the lateral propriobulbar projection system is derived primarily from the lateral part of the lateral tegmental field and innervates the ipsilateral hypoglossal nucleus whereas the medial propriobulbar projection system originates from the medial part of the lateral tegmentum and tends to project bilaterally to the hypoglossal nucleus (Holstege and Kuypers, 1977; Holstege et al, 1977).…”
Section: Discussionmentioning
confidence: 99%
“…It has long been recognized that tongue movements are comprehensively influenced by assemblies of integrated neuronal circuits located within the lower brainstem (Holstege and Kuypers, 1977; Holstege et al, 1977, 1983; Lowe, 1981; Jean, 1984, 2001; Miller, 1999; Sawczuk and Mosier, 2001; Jürgens, 2002; Gestreau et al, 2005; Hannig and Jürgens, 2005; Lund and Kolata 2006; Yamada et al, 2005). However, very little is known about the role of the cerebral cortex in mediating tongue movements which is quite surprising, since clinical observations have long noted that oromotor deficits occur in patients sustaining localized cortical injury (e.g., Meadows, 1973; Willoughby and Anderson, 1984; Horner et al, 1988; Robbins and Levin, 1988; Martin and Sessle, 1993; Robins et al, 1993; Daniels and Foundas, 1997; Hamdy et al, 1997).…”
Section: Introductionmentioning
confidence: 99%